APLIKASI PENTRACE UNTUK VULNERABILITY ASSESSMENT BERBASIS OWASP ZAP API - Putri, Aulia; Hayadi, Bambang Herawan; Pratama, Gelard Untirtha (Politeknik Bisnis Indonesia, 2025)
The increase in the number of cyber attacks in Indonesia highlights the need for adaptive and effective information security and vulnerability detection systems. This study aims to develop an Android application named PENTRACE capable of automatically assessing vulnerabilities by leveraging the OWASP ZAP API as the primary scanning engine. The methodology employed is Research and Development (R&D) using the Waterfall model approach, encompassing the stages of requirement analysis, design, implementation, testing, and evaluation. The application was built using Flutter and integrated with OWASP ZAP running on a virtual machine on Google Cloud Platform (GCP). The research results show that PENTRACE successfully detected various types of vulnerabilities such as SQL Injection, Cross-Site Scripting (XSS), and Remote Code Execution (RCE), and presented the scanning results in the form of visualizations. Additionally, the application provides a feature to download reports in PDF format. These findings indicate that PENTRACE is a practical, flexible, and sustainable mobile solution to effectively support the vulnerability assessment process.